Análise, avaliação e reestruturação financeira de uma indústria de médio porte brasileiro : um estudo de caso - Vieira, André Afonso (2007)
All the changes that came with the globalization have demanded to the organizations news management skills to face this extremely competitive environment. The current death index of the Brazilian companies shows their limitation to face this new scenario. The purpose of this present study is to suggest several alternatives to recover a middle-sized company that is facing a difficult financial situation. The first chapter presents an overview about the subject and the issues faced by smalls and middles-sized companies. The third chapter presents the theories about financials index, strategy and management control. The fourth chapter presents some implemented propositions and the progress of company s results. The fifth and last chapter presents the conclusion and recommendations for futures researches.